Hacking exposed 6 : network security secrets & solutions - McClure, Stuart; Scambray, Joel.; Kurtz, George (New York : McGraw-Hill, 2009)
Offers the most up-to-date guide to some of today's most detrimental hacks, techniques for preventing them, ways to avoid vulnerabilities, and procedures for putting a successful patch into the system.
Includes index.
rua 30/10/13
Loans
Keywords: Microsoft Windows (Computer file); Computer security; Computer networks -- Security measures; Data protection